Workforce Development in the US: Recent Trends and Evidence - Harry J. Holzer (Institute of Labor Economics (IZA), 2025)
In this paper, I examine what we know and don't know about both private and public workforce development in the US. I highlight three of the most important categories of programs and policy: a) Workforce development in accredited higher education institutions, particularly community colleges; b) Other publicly-funded or private training and services, including "sectoral training" that targets specific high-demand sectors of the economy; and c) On-the-job or work-based learning, including apprenticeships. I summarize the theoretical literature on workforce development and a broad landscape of the three key categories. I synthesize the empirical literature on workforce development, beginning with comparisons of different data sources, outcome measures and empirical methods used before reviewing the literature on estimated impacts in each of the three categories. I then consider the international evidence on workforce development, and how public efforts differ between the US and other industrial countries, before concluding.
Keywords: J24; 330; workforce; training; community college; sectoral; WIOA; apprenticeship work-based learning